Juridical Analysis of Non-Performing Loans at Regionally-Owned Rural Banks from the Perspective of State Financial Losses - Handhy Saputro Prabowo; Mukti Fajar Nur Dewata (Faculty of Law, Universitas Pekalongan, 2024)
The high level of non-performing loans (NPL) in regionally-owned Rural Banks (BPR), which reached 6.15% in June 2023, has the potential to cause state financial losses given that BPR's capital comes from the Regional Budget (APBD). This study aims to analyze the legal framework for non-performing loans in regional BPRs, to classify NPLs as either business risks or state financial losses, and to evaluate the effectiveness of the settlement mechanisms. The research method employs a normative juridical approach with statutory analysis. The findings indicate that non-performing loans can be categorized as state financial losses if caused by managerial negligence, abuse of authority, or collusion, based on Law No. 1 of 2004 on State Treasury and Law No. 17 of 2003 on State Finance. The effectiveness of the legal framework is still hindered by weak internal supervision, limited human resource capacity, and poor inter-agency coordination. The study recommends strengthening risk management systems, enhancing human resource capacity, and fostering stakeholder synergy to minimize state financial losses.